2013
DOI: 10.1212/wnl.0b013e31827dead9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal seizure outcome and prognostic predictors after hemispherectomy in 170 children

Abstract: The long-term seizure-free rates after hemispherectomy remained stable at 63% at 5 years and beyond. This study will assist in better candidate selection for hemispherectomy, presurgical counseling, and early identification of surgical failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
156
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 22 publications
(39 reference statements)
15
156
3
6
Order By: Relevance
“…The overall rate of seizure freedom was 73.4%, which is slightly higher than the rate of seizure freedom found by Holthausen et al 15 and comparable to other large, more recent series. 6,9,19,25,27,32,43 Long-term sustainability of seizure freedom is absolutely critical to justify surgery for epilepsy, which is (7) 10 (71) 2 (14) Sugimoto et al, 1999 1991-1996 Hospital for Sick Children Epilepsia (14) 33 (30) 51 (46) (continued) (27) 16 (33) 8 ( (44) 20 (21) 19 ( (42) 63 (34) 28 ( an irreversible intervention. Long-term seizure-free rates (≥ 5 years) following surgery for temporal lobe epilepsy are comparable to those reported in shorter-term studies.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of seizure freedom was 73.4%, which is slightly higher than the rate of seizure freedom found by Holthausen et al 15 and comparable to other large, more recent series. 6,9,19,25,27,32,43 Long-term sustainability of seizure freedom is absolutely critical to justify surgery for epilepsy, which is (7) 10 (71) 2 (14) Sugimoto et al, 1999 1991-1996 Hospital for Sick Children Epilepsia (14) 33 (30) 51 (46) (continued) (27) 16 (33) 8 ( (44) 20 (21) 19 ( (42) 63 (34) 28 ( an irreversible intervention. Long-term seizure-free rates (≥ 5 years) following surgery for temporal lobe epilepsy are comparable to those reported in shorter-term studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review 35 of large modern studies revealed overall Engel Class I outcomes in 541 (78.9%) of 686 patients who had undergone surgery for this condition. Resection is, in general, somewhat more successful than other epilepsy operations, such as hemispherectomy 25 for Rasmussen encephalitis (about 70% Engel Class I), SturgeWeber syndrome (same), or hemimegalencephaly (approximately 50% Engel Class I). Palliative epilepsy interventions, such as vagus nerve stimulator placement or corpus callosotomy, are less likely to result in seizure freedom.…”
Section: Nononcological Perspectivementioning
confidence: 98%
“…A longitudinal study of 170 patients looking into long-term prognosis after hemispherectomy reported that hypometabolic abnormalities on [18F]FDG-PET may be a more reliable marker of potential independent epileptogenesis in the contralateral hemisphere than the structural abnormalities seen on brain MRI [105].…”
Section: Pet [18f]fdg-petmentioning
confidence: 99%